Emergent ATM Banking in India: A study of Consumer Satisfaction - Baliyan, Deepa; Mittal, R. K. (Journal of Commerce and Trade, 2016)
TM Banking is a paramount product of e-banking system. Over the world there is drastic shift in banking practices from manual banking to paper less banking. The contribution of ATM to this level of paperless banking is widely recognized. Nowadays scope Banking industry become very wide it includes a number of businesses such as corporate banking, investment banking, wealth management, capital market etc. but on the other hand retail banking has its own identity it is a distinctive mass-market banking differentiated by a large customers and a large volume of transactions. Retail banking transactions are performed through ATM. So, ATM is becoming day by day popular not only in urban areas but also rural India. This plastic money touches life of every one in multiple ways. Present paper studies the satisfaction of ATM users (i.e. consumers) on the basis of various services provided by public and private sector banks.